The Landscape of AI in Indian Banking Sector: A Theoretical Perspective - Sarita Kumari Singh, Jayanta Kumar Parida, Sameer Shekhar (Journal of Informatics Education and Research, 2024)
This paper presents an in-depth study of the evolving role of Artificial Intelligence (AI) in the Indian banking sector, emphasizing its transformative impact on service delivery, operational efficiency, and customer engagement. Highlighting key advancements and integration of AI, the paper emphasizes on AI's crucial role in modernizing traditional banking practices and addressing contemporary challenges. It offers a balanced view by discussing both the opportunities AI presents for enhancing banking services and the challenges, including technical complexities and regulatory considerations. The future outlook section anticipates the continued growth of AI in banking, focusing on its potential to further personalize banking experiences and improve risk management. The study aims to provide a holistic view of AI's integration in Indian banking, serving as a resource for understanding the dynamic interplay between technological innovation and financial services.